EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN CONCEPT MAPS PADA MATERI PERSAMAAN GARIS LURUS DITINJAU DARI KECERDASAN EMOSIONAL SISWA KELAS VIII SMP NEGERI DI KABUPATEN SUKOHARJO TAHUN PELAJARAN 2014/2015 - Faizati, Khamsatul; Budiyono, Budiyono; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
using PBL with concept maps (CM), PBL, or classical learning, (2) which one gives better mathematics learning achievement, student with high, medium, or low emotional intelligence (EI) types, (3) which one is more effective for each learning model, student with high, medium, or low EI types,Â (4) which one is more effective for each EI type of students, using PBL with CM, PBL, or classical learning. This research used quasi experimental method with its population included all of students of state junior high school in Sukoharjo Regency. Sampling was done by stratified cluster random sampling. The size of the sample was 282 students. The data collection technique was the document that was national test in elementary school for initial capability data before the experiment, achievement test for mathematics student achievement data, and questionnaire of EI. The data were analyzed using analysis of variance. The conclusions of the research were as follows: (1) Mathematics achievement using PBL with CM is better than using PBL or classical learning. Likewise, mathematics achievement using PBL is as same as using classical learning. (2) Students with high EI have mathematics achievement better than students with medium or low EI. Likewise, students with medium and low EI have the same as mathematics achievement. (3) For each learning model, students with high EI have mathematics achievement better than students with medium or low EI. Likewise, students with medium and low EI have the same as mathematics achievement. (4) For each EI type of students, mathematics achievement using PBL with CM is better than using PBL or classical learning. Likewise, mathematics achievement using PBL is as same as using classical learning.Keywords: Problem Based Learning, concept maps, and emotional intelligence.